Towards Tailored Treatment: A Comparative Analysis of Schema Therapy And Dialectical Behavior Therapy For Borderline Personality Disorder - Shirin Abdallah Alimour; Majed Saleem El-Saleh; Mohammad Mahmoud Alrabeei; Brahmia Samira (Kurdish Studies, 2024)
This study aimed to enhance the response of individuals diagnosed with borderline personality disorder to two types of therapy: Schema Therapy and Dialectical Behavior Therapy. The primary objective was to predict treatment response and understand the mechanisms of change in BPD patients. A comprehensive randomized trial was conducted, involving 180 BPD patients who were randomly assigned to receive either Schema Therapy or Dialectical Behavior Therapy. The treatment phase lasted for one year. This study used the Zanarini Rating Scale for Borderline Personality Disorder (ZAN-BPD) to assess the change in BPD symptom severity. Secondary outcome measures included levels of depression and anxiety. Both Schema Therapy and Dialectical Behavior Therapy showed effectiveness in reducing the severity of BPD symptoms (with p-value < .05), and the mean difference of ST (11) is higher than the mean difference of DBT (4.07), which means Schema Therapy (ST) demonstrated a greater efficacy than Dialectical Behavior (DBT) in reducing borderline personality disorder (BPD). The analysis also concluded that there is an impact of these therapies on depression and anxiety levels. The findings of this study suggest that both Schema Therapy and Dialectical Behavior Therapy are effective in improving the response of BPD patients. Understanding the factors that predict treatment response, such as levels of functioning and comorbid conditions, can aid in tailoring treatment approaches for better outcomes. It is recommended that an additional investigation in this field has the potential to make a valuable contribution to the continuous advancement and enhancement of therapeutic interventions designed for individuals diagnosed with BPD. Ultimately, such research endeavors hold the promise of enhancing emotional well-being and general quality of life for these individuals.